Social issues and racism: homeless population and social assistance policy - Souza, Antonio Reguete Monteiro de; Escurra, Maria Fernanda (Argumentum, 2024)
The purpose of this article is to bring elements about the social issue in Brazil, linked to the phenomenon of structural racism, to problematize the existence of the homeless population, as a surplus segment of the working class, and the answers given through the Social Assistance Policy. To this end, at first, the conformation of free labor in Brazil is analyzed, its direct relationship with slavery and the way it was silenced, a key to the Brazilian social formation. Peculiar aspects of the development of capitalism in the country are pointed out, in order to identify how such characteristics are present in the Social Assistance Policy itself. Finally, we deal specifically with the homeless population and the Social Assistance Policy in the city of Rio de Janeiro, revealing structural racism in these dimensions.
Keywords: Social issues; Structural racism; Homeless Population; Social Assistance Policy